Construções [v1+ver] no português brasileiro contemporâneo sob perspectiva construcional - Robuste, Taísa Barbosa [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Esta tese é amparada por pressupostos gerais de teorias identificadas com correntes funcionalistas da linguagem (DIK, 1989, 1997; NUYTS, 2007; dentre outros), sobretudo o Funcionalismo da Costa Oeste Americana (TRAUGOTT, 2010; TRAUGOTT; DASHER, 2002; HOPPER; TRAUGOTT, 2003; GIVÓN, 1984, 1995; BYBEE, 2016; dentre outros), e conceitos específicos relacionados a teorias cognitivistas, especialmente a identificada com a Gramática de Construções (GOLDBERG, 1995, 2006; CROFT, 2001, 2007; LAKOFF, 1987), numa vertente que vem sendo denominada Modelos Baseados no Uso (BERLOW; KEMMER, 2000; BYBEE, 2016) ou Linguística Cognitivo-funcional (NUYTS, 2007). Mais diretamente, nos valemos de premissas da Gramática de Construções – que defende como princípio fundamental que a forma básica de uma estrutura sintática é a construção, considerada um pareamento simbólico de uma estrutura gramatical complexa com seu significado (GOLDBERG, 1995, 2006; CROFT, 2007) – para analisar, sob uma perspectiva sincrônica e com base em dados de língua escrita e falada do português brasileiro contemporâneo, as construções [v1+ver], sendo v1 substituível pelos verbos ir, querer e deixar. Partimos da hipótese de que essas construções resultam de um processo de construcionalização instanciado por uma série de micropassos de mudanças. A busca pela comprovação dessa hipótese perpassa o mapeamento das propriedades de composicionalidade, esquematicidade e produtividade das construções e permite cumprir o objetivo central da tese, que é o de explorar a relação entre mudança construcional, construcionalização e (inter)subjetivização (TRAUGOTT; TROUSDALE, 2013; TRAUGOTT; DASHER, 2002; TRAUGOTT, 2010). Identificamos e analisamos quatro usos das construções [v1+ver], quais sejam: i) Construções de movimento com propósito; ii) Construções perifrásticas de Tempo e Modalidade; iii) Construções modais epistêmicas; e, iv) Construções atuantes como Marcador Discursivo. Assumimos que diferenças no pareamento de forma e função entre essas construções são fortes evidências para atestar um possível processo diacrônico de construcionalização de [v1+ver]com valor (inter)subjetivo especializado na função de marcador discursivo atuante no fechamento de tópico ou de turno conversacional, no preenchimento de pausa e no engajamento do interlocutor.

This thesis is supported by general assumptions of functionalist-related theories of language (DIK, 1989, 1997, NUYTS, 2007, among others), especially the Functionalism of the American West Coast (TRAUGOTT, 2010, TRAUGOTT; DASHER, 2002; HOPPER; TRAUGOTT, 2003; GIVÓN, 1984, 1995; BYBEE, 2016; among others), and specific concepts related to cognitive theories, especially the one identified with the Construction Grammar (GOLDBERG, 1995, 2006; CROFT, 2001, 2007; LAKOFF, 1987), in a field that has been called Usage-Based Models of Language (BERLOW; KEMMER, 2000; BYBEE, 2016) or Cognitive-Functional Linguistics (NUYTS, 2007). More specifically, we rely on premises of the Construction Grammar, which holds as a fundamental principle that the basic form of a syntactic structure is the construction, conceived as a symbolic pairing of a complex grammatical structure and meaning (GOLDBERG, 1995, 2006, CROFT, 2007); we do so in order to analyze, from a synchronic approach, based on written and spoken language data from the contemporary Brazilian Portuguese, the constructions [v1+ver], being v1 replaceable by the verbs ir, querer, and, deixar. Our point of departures is the hypothesis that these constructions are the result of a constructionalization process that occurs through a series of micro-step changes. In order to prove this hypothesis, we map the compositionality, schematicity, and productivity properties of these constructions. This allows the accomplishment of the thesis’central objective: to explore the relation between constructional change, constructionalization, and (inter)subjectivization (TRAUGOTT; TROUSDALE, 2013, TRAUGOTT, DASHER, 2002; TRAUGOTT, 2010). We identify and analyze four uses of constructs [v1+ver], which are: i) Constructions of purposeful movement; ii) Tense and Aspect periphrastic constructions; iii) Modal epistemic constructions, and; iv) Discourse Marker Constructions. We assume that differences in form and function pairing between these constructs are strong evidence for attesting a possible diachronic constructionalization process of [v1+ver], with (inter)subjective value specialized in the discourse marker function, acting on topic closure or conversational shift in pause completion and speaker engagement.
[v1+ver] constructions in brazilian portuguese from a constructional perspective
Keywords: construcionalização; mudança construcional; verbo ver; constructionalization; constructional change; verb ver